Lagerstroemia x ’Tonto’ Tonto Crape Myrtle: FPS-329/FP329, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the ‘Tonto’ crape myrtle, a popular small tree known for its striking summer flowers, attractive fall foliage, and high drought tolerance. It details the plant’s characteristics, including its growth habits, leaf and flower features, and soil and light requirements. The document also discusses the plant’s uses in landscaping, its pruning needs, and its resistance to pests and diseases. Additionally, it highlights various cultivars of crape myrtle, noting their specific attributes and resistance to common issues like powdery mildew. Original publication date October 1999.